Characterization of a Poly‐4‐Vinylpyridine‐Supported CuPd Bimetallic Catalyst for Sonogashira Coupling Reactions. Issue 14 (30th May 2017) - Evangelisti, Claudio; Balerna, Antonella; Psaro, Rinaldo; Fusini, Graziano; Carpita, Adriano; Benfatto, Maurizio
Abstract: CuPd bimetallic solvated metal atoms (SMA) synthesized by metal vapor synthesis (MVS) technique and supported on poly‐4‐vinylpyridine (PVPy) resin, showed significantly higher catalytic activity in Sonogashira‐type carbon–carbon coupling reactions than the corresponding monometallic Cu and Pd systems as well as their physical mixture. The analysis of the bimetallic catalyst combining transmission electron microscopy techniques and X‐ray absorption fine structure (XAFS) spectroscopy revealed the presence of small Pd nanoparticles (d m =2.5 nm) while the analysis of the X‐ray absorption data, at the Cu K‐edge suggests the formation of thin and incomplete Cu oxide layers around the Pd‐rich cores. Abstract : Added activity : a poly‐4‐vinylpyridine resin‐supported CuPd bimetallic catalyst showing higher catalytic activity in Sonogashira coupling reactions compared to its monometallic counterparts, as well as their physical mixture, was characterized by TEM and XAFS.